Tradisi Makan Pinang Dalam Kesepakatan Perjanjian Di Desa Sanahu Kabupaten Seram Bagian Barat - Dyastuti, Risqi Mumpuni; Baharuddin, Wahdaniah (BAMETI Customary Law Review, 2023)
Customary agreements have their own legal provisions that are binding on their customary law communities. These customary rules are usually in the form of values that have been adhered to by the customary law community itself that have been implemented and applied to the customary law community for many years. This regulation is usually in oral form that has been normed to be used as a provision for the local customary law community and there are also written customary law regulations. This research is a non-doctrinal research, there are two types of data in the study, namely primary data and secondary data. Data collection techniques are carried out by means of interviews accompanied by interview guidelines. After obtaining data, it is grouped descriptively analytically by identifying and then grouping, then analyzed and described according to its hierarchy. Documents and library materials are descriptively analytical by identifying and then grouping, then reviewed and described according to their hierarchy. The tradition carried out in the country of Sanahu, Elpaputih District, West Seram Regency is the tradition of eating areca nut. This is done in order to fulfill the traditional traditions of the local country in implementing an agreement between communities. This ritual is carried out to preserve the culture in the country.